Fibrin clot characteristics and anticoagulant response in a SARS‐CoV‐2‐infected endothelial model. Issue 2 (22nd March 2022) - McCafferty, Conor; Lee, Leo; Cai, Tengyi; Praporski, Slavica; Stolper, Julian; Karlaftis, Vasiliki; Attard, Chantal; Myint, David; Carey, Leeanne M.; Howells, David W.; Donnan, Geoffrey A.; Davis, Stephen; et al.
Abstract: Coronavirus disease 2019 (COVID‐19) patients have increased thrombosis risk. With increasing age, there is an increase in COVID‐19 severity. Additionally, adults with a history of vasculopathy have the highest thrombotic risk in COVID‐19. The mechanisms of these clinical differences in risk remain unclear. Human umbilical vein endothelial cells (HUVECs) were infected with SARS‐CoV‐2, influenza A/Singapore/6/86 (H1N1) or mock‐infected prior to incubation with plasma from healthy children, healthy adults or vasculopathic adults. Fibrin on surface of cells was observed using scanning electron microscopy, and fibrin characteristics were quantified. This experiment was repeated in the presence of bivalirudin, defibrotide, low‐molecular‐weight‐heparin (LMWH) and unfractionated heparin (UFH). Fibrin formed on SARS‐CoV‐2 infected HUVECs was densely packed and contained more fibrin compared to mock‐infected cells. Fibrin generated from child plasma was the thicker than fibrin generated in vasculopathic adult plasma ( p  = 0.0165). Clot formation was inhibited by LMWH (0.5 U/ml) and UFH (0.1–0.7 U/ml). We show that in the context of the SARS‐CoV‐2 infection on an endothelial culture, plasma from vasculopathic adults produces fibrin clots with thinner fibrin, indicating that the plasma coagulation system may play a role in determining the thrombotic outcome of SARS‐CoV‐2 infection. Heparinoid anticoagulants were most effective at preventing clot formation.